High-grade soft tissue sarcoma arising in a desmoid tumor: case report and review of the literature. Issue 1 (December 2015) - Bertucci, François; Faure, Marjorie; Ghigna, Maria-Rosa; Chetaille, Bruno; Guiramand, Jérôme; Moureau-Zabotto, Laurence; Sarran, Anthony; Perrot, Delphine
Abstract Desmoid tumors are rare benign monoclonal fibroblastic tumors. Their aggressiveness is local with no potential for metastasis or dedifferentiation. Here we report on a 61-year-old patient who presented a locally advanced breast desmoid tumor diagnosed 20 years after post-operative radiotherapy for breast carcinoma. After 2 years of medical treatment, a high-grade undifferentiated pleomorphic soft tissue sarcoma arose within the desmoid tumor. Despite extensive surgery removing both tumors, the patient showed locoregional relapse by the sarcoma, followed by multimetastatic progression, then death 25 months after the surgery. The arising of a soft tissue sarcoma in a desmoid tumor is an exceptional event since our case is the fourth one reported so far in literature. It reinforces the need for timely and accurate diagnosis when a new mass develops in the region of a preexisting desmoid tumor, and more generally when a desmoid tumor modifies its clinical or radiological aspect.